Physical and chemical characteristics of refined vegetable oils from rubber seed (Hevea brasiliensis) and bread-fruit (Artocarpus altilis) - Achinewhu S C; Akpapunam M A
Crude vegetable oil obtained by solvent extraction from rubber seed (Hevea brasiliensis) and breadfruit (Artocarpus altilis) were subjected to alkali refining (neutralisation), degumming and bleaching. At each stage of refining, the crude and the refined oil were analysed for their physical and chemical characteristics notably specific gravity, moisture and volatile matter content, saponification, iodine values, peroxide value, unsaponifiable matter, fatty acids and free fatty acids. Results showed an improvement in the quality of the oil after refining. Refining decreased the free fatty acids and peroxide value, which are some of the characteristics that determine stability. There was a very slight decrease in saponification value and unsaponifiables matter after refining. Refining did not have much effect on the fatty acid composition except slight nonconsistent decreases in saturated and unsaturated fatty acids. There was no decrease in iodine value.
Keywords: Bread fruit oil; Chemical composition; Oil characteristics; Refined oils; Rubber seed; Rubber seed oil